THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF INDUSTRY AND TRADE SOUTH SULAWESI PROVINCE - Rifky A, Muhammad; Natsir, Uhud Darmawan; Dipoatmodjo, Tenri S.P; Sahabuddin, Romansyah; Burhanuddin (Journal Management & Economics Review (JUMPER), 2023)
The purpose of this study was to determine how work discipline affects employee performance at the Office of Industry and Trade of South Sulawesi Province. In this study, the population at the Office of Industry and Trade of South Sulawesi Province was 67 employees in 2023. The sample collection of this study was taken from the total population who had the characteristics of being Civil Servants (PNS). The number of populations that meet the sampling characteristics is 52 employees. The data analysis technique used is simple linear regression analysis using Statistical Product Servive Solution (SPSS). The results showed that there was a positive and significant effect of work discipline variables on work performance at the Department of Industry and Trade of South Sulawesi Province.